LINEAR DIFFERENCE COMPUTED TOMOGRAPHY SIZE LARGE MOLAR TEETH IN HEALTHY MEN FROM CENTRAL REGIONS OF UKRAINE - Shinkaruk-Dykovytska М.М.; Kotsyura О.О.; Tepla, T.O.; Melnik М.Р.; Chaika, V.G.; Shepitko, K.V.; Lykhytskyi O.М. (World of Medicine and Biology, 2018)
In 64 practically healthy men aged from 19 to 35 years from the central region of Ukraine, features of the differences in the computed tomographic size of large angular teeth and their roots, depending on the type of person, were determined. The most pronounced differences in the size of large angular teeth are set on the lower jaw for height, crown height, mesio-distal dimensions of the crown and neck, as well as the length of the near and far root of the right and left first and second teeth.